Micromechanical analysis of asphalt behaviour - García, Adriana de Jesús (2025)
Recent theories asphalt classified as a continuous matrix, which associations of polar molecules (asphaltenes and resins) dispersed in a fluid of molecules of lower molecular weight and polarity (aromatic and saturated). To better understand the behavior of asphalt a literature review, where it was observed that the most innovative methodology is the application of atomic force microscope, which allows to characterize materials nanomechanical scale was performed. AFM technique has been used in the last 20 years as one of the tools that combines the powerful capabilities of the latest generation of devices with atomic force spectroscopy full range of imaging modes available on its measurement: contact, noncontact and down force. Following this, they have achieved excellent results in the morphology of the asphalt binder, where different researchers have come to characterize a multi-phase asphalt defined as: to stage the katana-phase, perfase and salt-phase. The literature review was conducted in order to enrich the knowledge of the micromechanical behavior of asphalt binder, which then serve as the basis for determining and applying the indentation technique, which involves determining the value of stiffness modulus. Therefore micromechanical behavior analysis is an important tool for future research, which should focus on analyzing the properties of asphalt binder.